Photoresponsive Double Cross-Linked Supramolecular Hydrogels Based on A-Cyclodextrin/Azobenzene Host–Guest Complex - Liubimtsev, Nikolai; Zagradska-Paromova, Zlata; Appelhans, Dietmar; Gaitzsch, Jens; Voit, Brigitte (Macromolecular Chemistry and Physics, 2023)
Smart hydrogels are interesting materials as they can change their dimensions upon an external trigger. Herein, a photoresponsive double cross-linked hydrogel system based on polyacrylamide (AAm) with grafted poly(2-methyl-2-oxazoline) (PMOXA) chains with a α-cyclodextrin/azobenzene host–guest complex is present. Switching azobenzene from the trans to the cis-conformation through irradiation with UV light breaks the complex reversibly. Well-defined PMOXA macromonomers have been synthesized and functionalized with the respective host and guest functionalities as well as double bonds for the incorporation into the polymer network as grafted side chains. The chemical structure of the macromonomers and the complex is confirmed by 1H NMR, 2D NOESY NMR, GPC, and UV–VIS measurements. Hydrogels with different ratios of permanent and photoresponsive cross-linkers as well as different chain lengths of the PMOXA macromonomers are analyzed toward differences in their swelling/deswelling and elastic properties. Successive irradiation of supramolecular hydrogels with UV and VIS light allowed for a repeated swelling and de-swelling of the hydrogels. This system is studied at both macro and micro scales, showing similar swelling tendencies. The tuned properties of photoresponsive double cross-linked hydrogel makes this system a promising tool for various applications, for example, as in situ controllable valves in microfluidic flow cells.
CRIS-Team Scopus Importer:2023-03-20
Keywords: double cross-linked systems; photoresponsive hydrogels; smart microgels; supramolecular hydrogels; α-cyclodextrin